DISTAL FEMUR FRACTURE FIXED WITH LOCKING PLATE - Zulﬁqar Ahmad; Tariq Mahmood; Faisal Mahmood (Journal of University Medical & Dental College, 2017)
ABSTRACT: OBJECTIVE: To record the complications and clinical outcomes of locking plate used for the management of distal femoral fractures. METHODOLOGY: A total of 100 cases were selected for the treatment of distal femur shaft fracture. Closed or open reduction and internal ﬁxation of the supracondylar femoral fractures adopting supine position with the help of ﬂuoroscope was done. Each patient was treated according to the particular type of injury, associated injuries, location of the fracture and involvement of the soft tissue. Internal ﬁxation of the metaphyseal part of the fracture by adopting open or submuscular approach was performed. Patients mobilization was done on the basis of pattern of femur fracture and constellation of injuries. Until the signs of healing alongwith resolution of fracture lines or formation of callus, the weight bearing was delayed while the usual physical therapy was advised. The patients were followed up on a regular interval at 2, 6, 12 weeks, 6 months, 12 months and 24 months. Clinical examination was done for sensory and motor examination, knee stability, range of motion and ambulation was also performed. Radiographic examination was also done. We considered radiographic union as bridging of the fracture site at 3 cortices by callus or cortical continuity as well as obliteration of the fracture line. The delayed union was deﬁned as missing radiographic evidence of union of fracture with continued progress towards healing at six-month time whereas varus angulation >10° at fracture healing was deﬁned as malunion. RESULTS: Out of a total 100 cases of distal femur fracture, mean age of the patients was 53.47+4.78, (54% were male and 46% females). Motor vehicle accidents were recorded as 38%, low energy fall was found in 37%, 8% for motorcycle accident and high energy fall, 5% had unknown mechanism of injury while 4% had sports injuries. Final healing status reveal that 90% of the cases had healing, 4% had non-union, 4% had total knee replacement while antibiotic spacer after infection total knee replacement in 1% and 1% had below knee amputation. Clinical outcome o o(r ange of motion) according to Kristensen was recorded as 3% who had <60 , 18% had 60-94 , o o 10% had 95-104 while 64% had >104 and 5% had unknown or not applicable. CONCLUSION: Despite adopting modern techniques ﬁxation of locked periarticular plating, distal femoral fractures still result in poor clinical outcome and persistent disability. Further studies are required to determine the factors which may improve outcome.